Interleukin‐6 increases expression of serine protease inhibitor Kazal type 1 through STAT3 in colorectal adenocarcinoma. Issue 12 (14th December 2015) - Räsänen, Kati; Lehtinen, Elina; Nokelainen, Kristiina; Kuopio, Teijo; Hautala, Laura; Itkonen, Outi; Stenman, Ulf‐Håkan; Koistinen, Hannu
Abstract : Inflammation promotes colorectal cancer (CRC) tumorigenesis, but the underlying molecular mechanisms are still being uncovered. Proinflammatory cytokine interleukin‐6 (IL‐6) stimulates survival signaling in CRC; inflammatory signals also regulate production and activity of proteases and their inhibitors. Over‐expression of serine protease inhibitor Kazal type 1 (SPINK1) predicts an unfavorable outcome in colon cancer. The SPINK1 gene contains an IL‐6 responsive element, suggesting it could act as an acute phase reactant. We assessed the connection between IL‐6 and SPINK1, and the function and mechanism of this signaling. Our results show that Colo205 and HT‐29 cells express and secrete SPINK1, and both fibroblast‐derived and recombinant IL‐6 further increased the SPINK1 levels. Concurrently CRC cells augmented the IL‐6 production in fibroblasts. In CRC tissues cancer cells were positive for SPINK1, whereas IL‐6 was found in stromal cells. In Colo205 cells IL‐6 also stimulated the secretion of trypsin‐1 and ‐2, the key targets of SPINK1 protease inhibition, whereas in HT‐29 cells trypsin‐1 and ‐2 levels remained constantly low. Functionally, both IL‐6 and SPINK1 increased the motility of the CRC cells. Mechanistically, IL‐6 activated the canonical STAT3 pathway and inhibition of STAT3 phosphorylation decreased the levels of SPINK1, trypsin‐1 and ‐2. Taken together, our results indicate a novel link between inflammatory signals originating from the tumor microenvironment and increased SPINK1 levels. This finding has potential therapeutic implications for targeted therapy, as it confirms that SPINK1 acts as an acute phase reactant and that it participates in the paracrine crosstalk with the tumor microenvironment of colon cancer. © 2015 Wiley Periodicals, Inc.